Saccadic eye movement performance reduces visual manipulation influence and center of pressure displacements in older fallers - de Souza, Nathaly Freitas [UNESP]; Brito, Matheus Belizário [UNESP]; Rodrigues, Sérgio Tosi [UNESP]; Cavalieri, Beatriz Carvalho [UNESP]; Lima, Diego Nera [UNESP]; de Moraes, Rodolfo Lemes [UNESP]; Barbieri, Fabio Augusto [UNESP]; Barela, José Angelo [UNESP]; Polastri, Paula Fávaro [UNESP] (Springer Nature, 2022)
This study examined changes in postural control and gaze performance of faller and non-faller older adults under conditions of visual tasks and optical flow manipulations. Fifteen older non-fallers (69.8 years, ± 3.2) and fifteen older fallers (71.1 years, ± 6.4) stood on a force platform inside a moving room wearing an eye tracker. Four tasks were performed: gaze fixation; predictable saccades; unpredictable saccades; and free-viewing. The stimuli appeared at a frequency of 1.1 Hz during conditions of predictable and unpredictable saccades. Sixteen trials were divided into two blocks. In the first block, the room remained stationary. In the second block, the room oscillated, without the participant’s awareness, with a 0.6 cm amplitude and 0.2 Hz frequency. Results showed postural sway attenuation in older fallers during the saccadic tasks compared to gaze fixation and free-viewing tasks, in both stationary and moving room conditions. Both groups showed increased center of pressure (CoP) magnitude during the moving room condition and CoP displacements strongly coupled to the room’s movement. The influence of the moving room on the postural sway was reduced during the saccadic tasks for both older groups. Older fallers exhibited higher variability compared to older non-fallers. Gaze behavior differences between groups were dependent on the goals of the visual tasks. Therefore, CoP displacements of older adults are reduced during saccadic tasks regardless of their falling history. However, postural and gaze performance of older fallers suggests increased deterioration of postural and oculomotor control which may be used as a predictor of fall risk.
Keywords: Falls; Gaze; Older fallers; Optical flow; Postural control; Visual-motor coupling